CA19‐9 and apolipoprotein‐A2 isoforms as detection markers for pancreatic cancer: a prospective evaluation. Issue 8 (4th December 2018) - Honda, Kazufumi; Katzke, Verena A.; Hüsing, Anika; Okaya, Shinobu; Shoji, Hirokazu; Onidani, Kaoru; Olsen, Anja; Tjønneland, Anne; Overvad, Kim; Weiderpass, Elisabete; Vineis, Paolo; Muller, David; et al.
Abstract : Recently, we identified unique processing patterns of apolipoprotein A2 (ApoA2) in patients with pancreatic cancer. Our study provides a first prospective evaluation of an ApoA2 isoform ("ApoA2‐ATQ/AT"), alone and in combination with carbohydrate antigen 19–9 (CA19‐9), as an early detection biomarker for pancreatic cancer. We performed ELISA measurements of CA19‐9 and ApoA2‐ATQ/AT in 156 patients with pancreatic cancer and 217 matched controls within the European EPIC cohort, using plasma samples collected up to 60 months prior to diagnosis. The detection discrimination statistics were calculated for risk scores by strata of lag‐time. For CA19‐9, in univariate marker analyses, C‐statistics to distinguish future pancreatic cancer patients from cancer‐free individuals were 0.80 for plasma taken ≤6 months before diagnosis, and 0.71 for >6–18 months; for ApoA2‐ATQ/AT, C‐statistics were 0.62, and 0.65, respectively. Joint models based on ApoA2‐ATQ/AT plus CA19‐9 significantly improved discrimination within >6–18 months (C = 0.74 vs. 0.71 for CA19‐9 alone, p = 0.022) and ≤ 18 months ( C = 0.75 vs. 0.74, p = 0.022). At 98% specificity, and for lag times of ≤6, >6–18 or ≤ 18 months, sensitivities were 57%, 36% and 43% for CA19‐9 combined with ApoA2‐ATQ/AT, respectively, vs. 50%, 29% and 36% for CA19‐9 alone. Compared to CA19‐9 alone, the combination of CA19‐9 and ApoA2‐ATQ/AT may improve detection of pancreatic cancer up to 18 months prior to diagnosis under usual care, and may provide a useful first measure for pancreatic cancer detection prior to imaging. Abstract : What's new? A new biomarker may boost sensitivity of early pancreatic cancer testing. Because the disease is rare, and most cases arise sporadically, screening focused on patients with a family history is inadequate, but general‐population screening remains impractical. Here, the authors investigated a newly identified biomarker for pancreatic cancer, an isoform of apolipoprotein A2 called ApoA2‐ATQ/AT. They tested pre‐diagnosis blood samples collected from the EPIC cohort and looked at ApoA2‐ATQ/AT in combination with the commonly used biomarker, CA19‐9. Using both markers together enabled earlier detection of cancer than CA19‐9 alone, up to 18 months before diagnosis.